The efficiency analysis of thrombolytic rt-PA combined with intravascular interventional therapy in patients with acute basilar artery occlusion - Xianxian, Zhao (Int J Biol Sci, 2017)
In order to further optimize the treatment strategy for the patients with acute basilar artery occlusion, we were dedicated to study the therapeutic effects and influential factors in the process of treated basilar artery occlusion with thrombolytic combined vascular interventional therapy. 75 patients with acute basilar artery occlusion treated with arterial thrombolytic therapy were analyzed retrospectively. In accordance with the discharge records of patients, their short-term curative effect with 24-hour treatment and 14-days treatment were evaluated. Our data showed that the survival condition of the patients with acute acute basilar artery occlusion were visibly improved by combination thrombolytic and interventional therapy. Moreover, their BI scores were remarkably improved, while NIHSS and mRS scores were evidently reduced. These data proved that our treatment strategy was able to improve the survival condition of patients with acute basilar artery occlusion. Furthermore, our data showed that coagulation related factors remarkably improved in the patients, when they treated by combination thrombolytic therapy with interventional therapy. In addition, our results suggested that the patients' bilateral Babinski(+), revascularization and coma symptom were closely related to their prognosis after treated the patients with combination thrombolytic and vascular interventional therapy, and the difference was statistically significant (p<0.05, p<0.05, p<0.05). Besides, our data also displayed that the with stent assisted angioplasty was significantly superior to the patients with balloon angioplasty, and the difference was statistically significant (p<0.05). Anyhow, combination thrombolytic with interventional therapy can effectively promote the prognosis of the patients with acute basilar artery occlusion. The coma symptom, bilateral Babinski(+), and revascularization in the patients with acute basilar artery occlusion have an appreciable impact on the patients' prognosis.